The association between changes in depression/anxiety and trajectories of psychotic-like experiences over a year in adolescence - Yamasaki, Syudo; Foo, Jerome Clifford (Schizophrenia research, 2018)
Background - Recent cross-sectional studies suggest that psychotic-like experiences (PLEs) are associated with depression and anxiety in adolescents. While longitudinal studies have observed that adolescents suffer more severe symptoms of depression/anxiety when PLEs persist, it remains unclear whether depression/anxiety worsens or improves with PLE emergence or remission, respectively. In this prospective school-based study, we investigated the association between longitudinal changes in depression/anxiety and one-year PLE trajectories in adolescence. - Methods - Nine hundred and twelve adolescents participated in the baseline assessment of PLEs and depression/anxiety; 887 (97.3%) adolescents completed the follow-up assessment one year later. Multilevel analysis was conducted to evaluate the change in depression/anxiety, evaluated using the General Health Questionnaire-12 (GHQ-12), during the year according to PLE trajectory, adjusting for baseline depression/anxiety, gender, age, substance use and victimization. - Results - Sixteen percent of adolescents reported PLEs at baseline, with 56% of them remitting at follow-up. At follow-up, PLEs were experienced by 6.6% of adolescents not experiencing PLEs at baseline (incident PLE group). After adjusting for covariates, GHQ-12 score worsened significantly during the year in students with incident trajectories (regression coefficient for time, α1=1.91, 95% CI: 1.04-2.77), but in those showing remission, GHQ-12 score did not significantly improve (α1=−0.20, 95% CI: −0.97-0.56). - Conclusions - Greater awareness about PLEs and their trajectories in school health care settings may be a key towards the prevention and treatment of adolescent depression and anxiety.
Available online 19 October 2017
Gesehen am 22.04.2020